2018
DOI: 10.1037/pap0000161
|View full text |Cite
|
Sign up to set email alerts
|

The split narcissist: The grandiose self versus the inferior self.

Abstract: This article deals with the phenomenon of split personality and, specifically, with the split between the grandiose self and the inferior self, which is typical of pathological narcissism. While grandiosity is widely regarded as the dominant trait of the narcissist's personality and the diagnostic hallmark of narcissistic personality disorder, it is suggested that the 2 dissociated self-states-the grandiose self and the inferior self-are alternately dominant in, and equally characteristic of, the narcissistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…This relationship, as stated before, is also compatible with various perspectives that narcissistic individuals generally resort to other immature defense mechanisms, particularly the splitting defense (23,26). The splitting defense mechanism (β=0.46), which appears to be the strongest predictor of vulnerable narcissism in this study, functions to distinguish the opposing affections of grandiosity/superiority and insufficiency/ inferiority from each other in narcissistic individuals (70). However, Masterson (23) stated that unlike grandiose narcissism, emotional investments focus on the idealized object in the split intrapsychic structures of individuals with vulnerable narcissistic characteristics; in other words, they felt valued through the relationships they established with idealized important people by suppressing their grandiose feelings.…”
Section: Discussionsupporting
confidence: 89%
“…This relationship, as stated before, is also compatible with various perspectives that narcissistic individuals generally resort to other immature defense mechanisms, particularly the splitting defense (23,26). The splitting defense mechanism (β=0.46), which appears to be the strongest predictor of vulnerable narcissism in this study, functions to distinguish the opposing affections of grandiosity/superiority and insufficiency/ inferiority from each other in narcissistic individuals (70). However, Masterson (23) stated that unlike grandiose narcissism, emotional investments focus on the idealized object in the split intrapsychic structures of individuals with vulnerable narcissistic characteristics; in other words, they felt valued through the relationships they established with idealized important people by suppressing their grandiose feelings.…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, narcissism can be categorized into two types: grandiose (i.e., an unrealistic sense of superiority) and vulnerable (i.e., a constant victimisation mentality requiring sympathetic attention), which are alternately dominant. Each type of narcissism predicts different types of violence, the former being more active denigration of others, and the latter being a form of apparent self-belittlement at the emotional cost of others (Afek, 2018). It was also found that cyber-aggression had a positive correlation to narcissism 6 .…”
mentioning
confidence: 93%
“…Most importantly, it allowed us to investigate processes immediately after stimulus onset. Thus, this approach provided insights into rather automatic responses that are difficult or impossible to detect with other methods often applied in the research on narcissism, such as self-report (Tamborski & Brown, 2011 ), clinical observations (Afek, 2018 ) or fMRI (Jauk et al, 2017 ). Specifically, the current study used two well-studied components of the ERP associated with face processing: P1 and N170.…”
mentioning
confidence: 99%